The substantial transformation of the concept "existential" in modern philosophical journalism - Kateryna Gorbenko (Cхід, 2018)
The article is devoted to the analysis of substantial transformations of existential concept which has arisen within an existentially phenomenology of ontology to M. Heidegger. The relevance of a problem is that in modern philosophical journalism the corresponding concept is used absolutely in other sense. It has basic excellent from the Heidegger's semantic loading. Existence of two parallel philosophical discourses, one of which is placed emphasis on textual criticism, another - on those new horizons which is opened before thinkers owing to variations on exsistentials is stated. It is specified that after K. Jaspers's criticism, M. Heidegger has stopped trying a strict definition of exsistentials and their classifications which would turn them into categories. It is proved that only on condition of an exit out the personalism limits the concept "exsistentials" begins to work in a new, social and philosophical context